PEMANFAATAN KANAL YOUTUBE "DONGENG KITA" SEBAGAI MEDIA PEMBELAJARAN TEKS HIKAYAT KELAS X - Nugroho, Wahyu; Septiana, Ika; Kismiyati, Sri (Jurnal Membaca Bahasa dan Sastra Indonesia, 2024)
The utilization of the YouTube platform in the context of the "Dongeng Kita" channel as a medium for teaching narrative texts for class X has been the focus of this research. In this digital era, innovative and relevant learning approaches to meet the needs of the millennial generation are crucial. This research aims to explore how the YouTube platform can be effectively integrated into the teaching of narrative texts in class X, as well as to identify its impact on students' understanding and learning interest. The implications of this research underscore the importance of harnessing digital technology, particularly the YouTube platform, as a motivating and enriching learning tool for students. Teachers need to pay attention to the content presented to align with curriculum requirements and students' characteristics. This research contributes to the literature on the utilization of digital media in the context of education in Indonesia.